CRISPR/Cas9-generated mouse model with humanizing single-base substitution in the Gnao1 for safety studies of RNA therapeutics - Polikarpova, Anna V.; Egorova, Tatiana V.; Lunev, Evgenii A.; Tsitrina, Alexandra A.; Vassilieva, Svetlana G.; Savchenko, Irina M.; Silaeva, Yuliya Y.; Deykin, Alexey V.; Bardina, Maryana V. (Frontiers in Genome Editing, 2023)
The development of personalized medicine for genetic diseases requires preclinical testing in the appropriate animal models. GNAO1 encephalopathy is a severe neurodevelopmental disorder caused by heterozygous de novo mutations in the GNAO1 gene. Missense mutation GNAO1 c.607 G>A (p.Gly203Arg) is one of the most common pathological variants and likely results in the toxic activity of the encoded Gαo protein. As an innovative approach, sequence-specific RNA-based therapeutics such as antisense oligonucleotides or effectors of RNA interference are potentially applicable for selective suppression of the mutant GNAO1 transcript. While in vitro validation can be performed in patient-derived cells, a humanized mouse model to rule out the safety of RNA therapeutics is currently lacking. In the present work, we employed CRISPR/Cas9 technology to introduce a single-base substitution into exon 6 of the Gnao1 to replace the murine Gly203-coding triplet (GGG) with the codon used in the human gene (GGA). We verified that genome-editing did not interfere with the Gnao1 mRNA or Gαo protein synthesis and did not alter localization of the protein in the brain structures. The analysis of blastocysts revealed the off-target activity of the CRISPR/Cas9 complexes; however, no modifications of the predicted off-target sites were detected in the founder mouse. Histological staining confirmed the absence of abnormal changes in the brain of genome-edited mice. The created mouse model with the “humanized” fragment of the endogenous Gnao1 is suitable to rule out unintended targeting of the wild-type allele by RNA therapeutics directed at lowering GNAO1 c.607 G>A transcripts.